Induction of callus from phaleria macrocarpa / Izzatul Zuliana Zolkefli - Zolkefli, Izzatul Zuliana (2016)
Phaleria macrocarpa is herb plants in which each part of the plant has pharmaceutical value. Phaleria macrocarpa is known to cure diabetic, cancer and hypertension. The main objectives of this study are to determine the percentage of clear culture of Phaleria macrocarpa leaves after surface sterilization and to observe effects of different media treatments for callus induction. Surface sterilization of leaves explants using 20% Clorox produced 23.33% of clean culture. The remaining cultures were contaminated with fungi (53.33%) and bacteria (23.33%). Bacterial contamination was first observed after 3 days of culture whereas fungi contamination was first observed after 5 days of culture. The callus initiation was first observed after 3 weeks in treatment 1 (MS 0+1.0 mg/L NAA), treatment 3 (MS 0+3.0 mg/L NAA), treatment 2 (MS 0+2.0mg/LNAA) and treatment 6 (MS 0+3.0 mg/L NAA+0.5 mg/L BAP). Unfortunately, the other treatments which are treatment 4 (MS 0+1.0 mg/L NAA+0.5 mg/L BAP) and treatment 5 (MS 0+2.0 mg/L NAA+0.5 mg/L BAP) were contaminated. Thus no callus observation can be made. As a conclusion, from 60 explants of all treatment, only 15% responded to callus induction.